The influence of peer education on mother's self efficacy in providing nutrition with the nutritional status of toddlers in the Sei Musam Langkat - Kismi Asih Adethia; Ingka Kristina Pangaribuan; Debby Mayang Sari; Ade Rachmat; Mesrida Simarmata (Science Midwifery, 2023)
Infancy is the most important phase. Toddlers who don't get good nutrition can cause growth and development disorders. Self-efficacy is the belief and ability of a mother in providing nutrition. The low self-efficacy is due to the mother's lack of knowledge, the mother is not confident in her abilities. Efforts that can be made to increase self-efficacy by using a peer education approach are carried out with peer discussions so that mothers of toddlers can share and absorb information about providing nutrition. Aim: analyzing the Effect of Peer Education on Mother's Self Efficacy in Providing Nutrition with Toddler Nutritional Status. Method: This research uses a quasi-experimental research design with a pre-experimental design, one group pre-test and post-test design. Results: Education: majority of high school 61 people (82.4%), Occupation: Majority of housewives 48 people (64.9%), self efficacy majority not good 45 people (60.8%) Conclusion: The Influence of Peer Education on Mother's Self Efficacy in Providing Nutrition with the Nutritional Status of Toddlers